Advancing the pathologic phenotype of giant axonal neuropathy: early involvement of the ocular lens - Diane Armao; Thomas W. Bouldin; Rachel M. Bailey; Jody E. Hooper; Diana X. Bharucha; Steven J. Gray (Orphanet Journal of Rare Diseases, 2019)
Abstract Giant axonal neuropathy (GAN; ORPHA: 643; OMIM# 256850) is a rare, hereditary, pediatric neurodegenerative disorder associated with intracellular accumulations of intermediate filaments (IFs). GAN knockout (KO) mouse models mirror the IF dysregulation and widespread nervous system pathology seen in human GAN. Validation of therapeutic efficacy and viral vector delivery systems with these GAN KO models has provided the springboard for the development of a viral vector being delivered intrathecally in an ongoing Phase I gene therapy clinical trial for the treatment of children with GAN (https://clinicaltrials.gov/ct2/show/NCT02362438). During the course of a comprehensive pathologic characterization of the GAN KO mouse, we discovered the very early and unexpected involvement of the ocular lens. Light microscopy revealed the presence of intracytoplasmic inclusion bodies within lens epithelial cells. The inclusion bodies showed strong immunohistochemical positivity for glial fibrillary acidic protein (GFAP). We confirmed that intracytoplasmic inclusion bodies are also present within lens epithelial cells in human GAN. These IF inclusion bodies in lens epithelial cells are unique to GAN. Similar IF inclusion bodies in lens epithelial cells have not been reported previously in experimental animal models or human diseases. Since current paradigms in drug discovery and drug repurposing for IF-associated disorders are often hindered by lack of validated targets, our findings suggest that lens epithelial cells in the GAN KO mouse may provide a potential target, in vivo and in vitro, for evaluating drug efficacy and alternative therapeutic approaches in promoting the clearance of IF inclusions in GAN and other diseases characterized by intracellular IF accumulations.